Science Experiments: Reaching Out to Our Users. - Maureen Nolan; Stephanie Wright; Matthew Parsons; Lori Tschirhart; Laura Barrett; Linda Whang (Issues in Science and Technology Librarianship)
The authors discusses the experiments they conducted at the University of Washington (UW) on both traditional and unconventional methods of reaching out to library users. Among the efforts tried by the authors were going outside of a library to meet users in their spaces and employing virtual library on the Internet. Another method is an adventure game called geocaching intended for global positioning systems (GPS) users. The authors cited social networking as an easy approach to reach out to library users.